Odvetništvo in odvetniška tarifa v Sloveniji - Brezovnik, Boštjan; Oplotnik, Žan Jan; Mlinarič, Franjo (2017)
Attorneys and Attorney Tariff in Slovenia. In Slovenia, attorneys as part of the justice system represent an autonomous and independent service that is regulated by law. As set out in the decision of the Constitutional Court of RS, there is no doubt that the legislature has to adopt the law to regulate the attorneys' profession, but in its attempt of such regulation, the legislature always collides with the constitutional requirement that the attorneys are autonomous and independent. Therefore, when regulating the attorneys' profession, the legislature has to address the issues of autonomy and independence, and thus also the question of determining attorney tariffs, while certain issues must be left to be autonomously regulated within the attorneys' profession. The attorney tariff does not determine a mandatory price of legal services because an attorney and his client may always reach an agreement that is different from the attorney tariff. However, the tariff is binding when the court decides on the obligation to reimburse the party who has succeeded in a dispute for their attorney costs. With our research, we have empirically demonstrated that the existing attorney tariff in Slovenia unjustifiably drains smaller law firms, which guarantee an efficient coverage of population and smaller undertakings with a network of legal services. As a result, the economic autonomy and independence of law firms are compromised and the right to effective judicial protection is unjustifiably restricted for the parties who succeed in a dispute.
Keywords: public finance; attorney tariff; the right to effective judicial protection; financial analysis; Balassa-Samuelson effect; Slovenia